Practice of Fire-dragon moxibustion and key points in moxibustion temperature control (火龙灸技术操作和温度控制要点经验总结) - YAO Deming (姚德明) (中西医结合护理)
Dragon-fire moxibuston is known as a typical type of Traditional Chinese Medicine-separated moxibustion on Du meridian and bladder channel. This paper summarized the practice of Fire-dragon moxibustion and key points in moxibustion temperature control, in order to promote the clinical use of standard dragon-fire moxibuston. (火龙灸是在督脉和膀胱经施以隔物灸, 用于防治疾病灸法之一。本研究总结隔姜火龙灸技术操作以及温度控制要点, 以期推动火龙灸的临床应用, 并为规范有效的火龙灸技术操作提供参考。)